A University Student Suicide with Possible Copycat Features: A Forensic Case Report - Pratiwi, Baiq Annisa; Bumi Agung, I Gusti Lanang; Setiawardani, Alvina; Yudianto, Ahmad; Sumino, Renny; Ramadhani, Prasillia (International Journal of Medical Toxicology and Forensic Medicine, 2026)
intersection of public health and forensic science. Many students face intense academic pressure, emotional burden, and social instability, all of which can contribute to suicidal thoughts and actions. One particularly troubling aspect is the “copycat” phenomenon, where exposure to another person’s suicide, whether through media, social networks, or personal connections. Those all can lead to imitative behavior, especially among young people. Although this effect is recognized worldwide, there is a lack of detailed forensic documentation in Southeast Asia. Case Presentation: This report examines the case of a 20-year-old female undergraduate who died after a fail. The external examination revealed multiple healed scars on her forearm, indicating a history of self-harm, and severe head injuries consistent with a high-impact fall. Friends reported that she had recently sent messages that sounded like farewells, and there were rumors of a previous suicide at a nearby institution. The presence of similar stressors, a history of self-harm, and contextual similarities suggest that the possibility of a copycat effect should not be overlooked, even if a direct link cannot be confirmed. Conclusion: This case highlights the urgent need for thorough forensic investigations and stronger mental health support systems on university campuses. Preventing suicide contagion among students requires not only careful documentation but also responsible media reporting and targeted interventions for those at risk. By addressing these factors, we can work towards reducing the spread of suicide and protecting vulnerable students.